Study on Fault Activation Evaluation Mechanism and Sensitivity Analysis in Shale Gas Hydraulic Fracturing - Penglin Liu; Haifeng Fu; Zhuxing Chen; Qixuan Li; Jun Li; Jiayi Liu; Yu He; Xianbo Liu (Geofluids)
Shale gas hydraulic fracturing usually activates nearby faults and makes them slip. In horizontal wells, fault slip can result in serious casing deformation. Casing deformation slows the fracturing process, lowers production, and raises the cost of a shale gas well. It is challenging to obtain underground data on fault activation because of the deep shale reservoirs. As a result, the current study needed to indicate how hydraulic fracturing affects fault activation length. This made it challenging to control casing deformation. The fluid-structure coupled finite element method was used in this study to create a coupled seepage-stress model for heterogeneous shale formation. With microseismic signs and hydraulic fracking for shale gas, this model examined the variation law of pore pressure and ground stress. The fault activation coefficient was created to assess the fault activation duration and the impact of hydraulic fracturing. The model was verified by the microseismic signal. The outcomes of the numerical simulation demonstrate how the rapid rise in formation pore pressure during hydraulic fracturing affected the ground stress at the fault interface. The influence of ground stress variation at the fault interface on fault activation could not be ignored. Increased fault elastic modulus, fracture pressure, fracture time, and the fault Poisson ratio result in longer fault activation lengths. The length of the fault’s activation was decreased by the increase in fracture stage, distance from the fault, friction angle within the fault, and fault angle. Finally, a shale gas horizontal well with casing deformation in block C was analyzed. The results showed that reducing the fracturing duration can reduce the activation length of the fault by 68.25%, resulting in a 9.1 mm fault slide and a 0.86 mm casing deformation, respectively. This study offers theoretical guidelines for preventing fault activation during hydraulic fracturing in horizontal shale gas wells.